Plasma levels of platelet-enriched microRNAs change during antiplatelet therapy in healthy subjects - Krammer, Teresa L.; Kollars, Marietta; Kyrle, Paul A.; Hackl, Matthias; Eichinger, Sabine; Traby, Ludwig (Frontiers in Pharmacology, 2022)
Platelets are the main effectors of primary hemostasis but also cause thrombosis in pathological conditions. Antiplatelet drugs are the cornerstone for the prevention of adverse cardiovascular events. Monitoring the extent of platelet inhibition is essential. Currently available platelet function tests come with constraints, limiting use in antiplatelet drug development as well as in clinical routine. With this study, we aim to investigate whether plasma miRNAs might be suitable biomarkers for monitoring antiplatelet treatment. Platelet-poor plasma was obtained from a trial including 87 healthy male volunteers that either received ticagrelor (n = 44) or clopidogrel (n = 43). Blood was collected before drug intake and after 2 h, 6 h, and 24 h. We measured a panel of 11 platelet-enriched miRNAs (thrombomiRs) by RT-qPCR and selected four biomarker candidates (i.e., miR-223-3p, miR-150-5p, miR-126-3p, miR-24-3p). To further characterize those miRNAs, we performed correlation analyses with the number of extracellular vesicles and clotting time dependent on procoagulant vesicles (PPL assay). We show that platelet-enriched miRNAs in the circulation are significantly reduced upon P2Y12-mediated platelet inhibition. This effect occurred fast, reaching its peak after 2 h. Additionally, we demonstrate that higher baseline levels of thrombomiRs are linked to a stronger reduction upon antiplatelet therapy. Finally, we show that miRNAs from our panel might be the cargo of platelet-derived and procoagulant vesicles. In conclusion, we provide evidence that thrombomiR levels change within 2 h after pharmacological platelet inhibition and circulate the body within platelet-derived and procoagulant extracellular vesicles, rendering them potential biomarker candidates for the assessment of in vivo platelet function.